Tempeh-Anchovy Sausage as a Snack Source of Calcium to Reduce Stunting - Devriany, Ade; Ori Pertami, Enardi; Ratih Puspita Kusumadewi, Purba; Zenderi, Wardani; Sumarto; Nainggolan, Lestarida; Agni Wiyatami, Monia (Poltekita: Jurnal Ilmu Kesehatan, 2024)
The fulfillment of good nutrition for breastfeeding will affect mothers' nutritional status and their babies' growth and development. The intake and nutrition of food consumed will influence the quality of breastfeeding given by breastfeeding mothers. Sausage innovation made from tempeh and bilis is expected to be a choice of distraction that can meet the needs of breastfeeding. The purpose of this study was to compile information on the nutritional value of sausage as an alternative food for handling stunting for breastfeeding mothers. This research is a type of experimental research in food production. The research design used with a randomized block design (RBD) is one factor in testing macro and micronutrients. Breastfeeding mothers who consume one of these dishes can meet total energy needs (223 kcal) by meeting the most excellent calcium, sodium, and fat needs. One dish of sausage products provides 19% of daily needs for fat and 11.8% for protein. The fulfillment of calcium needs reaches 92%, which means it has almost reached the recommended intake for the needs of breastfeeding mothers. Consuming sites as a distraction for breastfeeding mothers can meet the mother's daily needs for fat, protein, vitamin A, vitamin B3, calcium, iron, iodine, sodium, and copper. Sausage food products are proven to be an alternative food for handling stunting for breastfeeding mothers because they can meet the need for more nutrients when consuming sausage one day off.